Decreased susceptibility of melanized Cryptococcus neoformans to UV light. - Wang, Y (1994)
Melanized Cryptococcus neoformans cells were less susceptible than nonmelanized cells to the fungicidal effects of UV light. Phenoloxidase-catalyzed production of melanin-like pigments may serve to protect the fungus against ionizing radiation.